Coordination in the agri-food sector: The role of social capital and remoteness in the emergence of Italian network contracts. (July 2020) - Pagliacci, Francesco; Zavalloni, Matteo; Raggi, Meri; Viaggi, Davide
Abstract: The organization of the agri-food sector is dominated by hybrid forms of interaction among independent firms. To explain the participation in this form of arrangements, the bulk of the literature has focused on firm-level characteristics. In this paper, we assess the role that the territorial dimension, in terms of social capital and geographical remoteness, plays in the explaining Italian firms' participation to Network Contracts (NC). NC have been institutionalized in Italy in 2009 to provide a legal framework for the formation of a wide range of hybrids, encompassing both vertical and horizontal coordination. Data on the population of NCs are aggregated at the municipality level and analyzed through a zero-hurdle model, that properly addresses skewed data with many zeros and admits different underlying processes to explain the zero values. Results show that the territorial dimension plays a major role in explaining the participation to NCs. Proxied through a synthetic indicator, the social capital is strongly significant and negatively related to the number of NC members at the municipality level. However, such a relation proves to be more complicated when different dimensions of social capital are taken into account and when trying to disentangle its effect on horizontal and vertical NC. With respect to geography, remoteness seems to hinder the formation of NCs, as the more peripheral a given municipality, the lower the number of participants. NCs seems to be a legal framework that is able to overcome the constraint to coordination set by the lack of social capital, but it does not show to overcome the problem related to remoteness. Highlights: We analyse the territorial determinants of joining a Network Contracts in Italy. Network Contracts provide a legal basis for the creation of horizontal and vertical hybrids. The relationship between Network Contracts and social capital endowment is complex. Remoteness of areas is negatively related to participation to Network Contracts.